Design of the State Feedback-Based Feed-Forward Controller Asymptotically Stabilizing the Overhead Crane at the Desired End Position - Vrabel, Robert (Journal of Applied Nonlinear Dynamics, 2026)
The problem of feed-forward control of overhead crane system is discussed. By combining the Kalman’s controllability theory and Hartman-Grobman theorem from the dynamical system theory, a linear, continuous state feedback-based feed-forward controller that stabilizes the crane system at the desired end position of payload is designed. The efficacy of proposed controller is demonstrated by comparing the simulation experiment results for overhead crane with/without time-varying length of hoisting/lowering rope.